PENGARUH INTELLECTUAL CAPITAL, TATA KELOLA PERUSAHAAN DAN KUALITAS AUDIT TERHADAP MANAJEMEN LABA - Nawang Kalbuana; A. Nugroho Budi R; Nita Yulistiani (Universitas Pamulang, 2020)
Earnings management is defined as earnings engineering activities / actions with certain objectives carried out by management. This research is expected to obtain empirical evidence of the influence of intellectual capital, corporate governance and audit quality in influencing earnings management in transportation companies and was listed on the Indonesia Stock Exchange in 2014-2018. Data was collected using a purposive sampling method and there were 14 companies that met the research criteria and carried out by testing the multiple linear regression hypothesis through the application of SPSS 23. In this study produced variables of intellectual capital, corporate governance and audit quality simultaneously have an influence on earnings management. While partially only intellectual capital variables that affect earnings management. Companies that are audited by large KAPs may not be able to limit the occurrence of earnings management actions. The large share ownership should be able to make the institutional control of operational activities, but the reality of institutional ownership is not able to limit the existence of earnings management. Theoretical implications expected from research are able to make intellectual capital as one indicator in measuring the occurrence of earnings management in future research. Keywords: Intellectual Capital; Institutional Ownership; Managerial Ownership; Audit Quality; Earnings Management